The effectiveness of Bacopamonnieri (Linn.) Wettst. as a nootropic, neuroprotective, or antidepressant supplement: analysis of the available clinical data - Brimson, James M. (Sci Rep, 2021)
Bacopa monnieri (Linn.) Wettst. has been used in traditional medicine as a drug to enhance and improve memory. In this regard, this study aims to provide B. monnieri's efficacy as a neuroprotective drug and as a nootropic against various neurological diseases. Literatures were collected, following Prisma guidelines, from databases, including Scopus, PubMed, Google Scholar, and Science Direct and were scrutinized using a quality scoring system. Means, standard deviations and ‘n’ numbers were extracted from the metrics and analyzed. Jamovi computer software for Mac was used to carry out the meta-analysis. The selected studies suggested that the plant extracts were able to show some improvements in healthy subjects which were determined in Auditory Verbal Learning Task, digit span-reverse test, inspection time task and working memory, even though it was not significant, as no two studies found statistically significant changes in the same two tests. B. monnieri was able to express modest improvements in subjects with memory loss, wherein only a few of the neuropsychological tests showed statistical significance. B. monnieri in a cocktail with other plant extracts were able to significantly reduce the effects of Alzheimer’s disease, and depression which cannot be solely credited as the effect of B. monnieri. Although in one study B. monnieri was able to potentiate the beneficial effects of citalopram; on the whole, currently, there are only limited studies to establish the memory-enhancing and neuroprotective effects of B. monnieri. More studies have to be done in the future by comparing the effect with standard drugs, in order to establish these effects clinically in the plant and corroborate the preclinical data.